AB0664 DIAGNOSIS DELAY IN ANKYLOSING SPONDYLITIS PATIENTS IN EGYPT: FACTORS, SOCIOECONOMIC AND CLINICAL OUTCOME. (2nd June 2020) - Abdelrahman, F. I.; Mortada, M.
Abstract : Background: Ankylosing spondylitis (AS) is a destructive inflammatory disease which was reported to have the longest diagnostic delay among the inflammatory rheumatic disease. This lag period have a great impact on the clinical outcome and socioeconomic state of the patients. With the advent of tumor necrosis factor-α (TNF-α) inhibitors, early diagnosis in AS has become important(1). Objectives: to evaluate the period from symptom onset to diagnosis of AS in Egyptian patients and to examine possible reasons for delayed diagnosis and its impact on the economic and social life of the patients. Methods: The study included 87 AS patients diagnosed according to the Assessment of Spondyloarthritis international Society (ASAS) criteria (2). A face-to-face interview was applied to take medical history, and a questionnaire that contains some clinical aspects of disease was used. Diagnosis delay was described as the gap between first AS symptom and correct diagnosis of AS. Clinical and functional assessment of axial SpA measured by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI). The direct medical cost during years of delay (including costs of medical consultations, medications, investigations, physiotherapy and surgical treatment) had been estimated by Egyptian pound. Results: The study included 87 AS patients with mean age (30.03±8.3), 70 male (80.5%) and 17 female (19.5%). Mean delay in diagnosis was(5.7 ±4.9) years. Mean of diagnostic delay for patient diagnosed before 2010 is (14±4.4) and that of patients diagnosed after 2010 is (3.5±1.8) with significant difference between both (p value<0.0001). The main cause of delay was incorrect diagnosis as follow degenerative disc disease (43/87, 49.4%), non-specific back pain (31/87, 35.6%), rheumatoid arthritis (10/87, 11.5%), rheumatic fever (2/87, 2.3%) and tuberculosis of spine (1/87, 1.1%). The mean of the medical visits was (6±5.4). Most incorrect initial diagnoses were made by orthopedicians (57.9%), followed by neurologists (22.2%) followed by rheumatologist (10%) and general phyisicians (9.9%). Absence of extra-articular manifestations, negative family history and juvenile age are significantly associated with diagnostic delay. Delay in diagnosis is significantly associated with higher disease activity index(BASDAI), functional index (BASFI), and damage index(BASMI). The mean of the costs during years of delay is (15671.3±546.1) with the mean of cost per each year delay (660.9±6.6) with high significant association between the cost and longer delay in diagnosis (<0.0001). Regarding work ability, we found that(32.2%) are fit for work, unfit (29.9%), partially fit (37.9%) with high significant difference between ability of work and shorter delay. Regarding social effect, 40.2 % of patients developed negative effect on social life with significant association to diagnostic delay (0.004). Conclusion: Our study confirmed the importance of early diagnosis of AS due to its impact on patient's health outcome and socioeconomic state.We recommend to increase the awareness about the disease among healthcare professionals in our region. References: [1]Sykes M. et al: Diagnostic delay in patients with rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis; Ann Rheum Dis.2015;74:e44. [2]Rudwaleit M. et al: The development of Assessment of Spondyloarthritis international Society classification criteria for axial spondyloarthritis; Ann Rheum Dis, 68 (2009), pp.777-783. Disclosure of Interests: None declared